DAMPAK PENETAPAN DESA WISATA TERHADAP PEREKONOMIAN MASYARAKAT (STUDI DI DESA BUNGIN KECAMATAN ALAS KABUPATEN SUMBAWA - Nur Azizah; Subhan Purwadinata; I Ismawati (Pusat Riset dan Publikasi, 2023)
This study aims to know the impact Bungin tourism village establishment on the communities economy of Sumbawa district. The type of this study was comparative study that used to compare the economy of the Pulau Bungin Village communities before and after being designated as tourist village. The total of population in this study were 3.171. The technique of determining the sample used was Slovin formula so that the numbers of samples in this study were 100. The method used to collect data was interviews. The data analysis technique used was the two-average difference test analysis technique or paired samples t-test. Based on the results of the research that has been done, it can be concluded that there are significant differences in the economy of the people of Bungin Island Village before and after its establishment as a tourist village in Sumbawa Regency. The average economic level of the people of Bungin Island Village has increased after being designated as a tourist village compared to before being designated as a tourist village.